2021
DOI: 10.1177/17479541211055690
|View full text |Cite
|
Sign up to set email alerts
|

Values, motivational orientation and team cohesion amongst youth soccer players

Abstract: There is a close link between moral education and sports activities. A well-organized sport can be an excellent means of transferring positive values to children and adolescents, which can influence motivation and group processes. This study aimed to analyse (a) the relationships between social, personal and individualistic values, motivational orientation and team cohesion amongst young soccer players and (b) compare differences in these variables between players competing in different age categories. Our par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…This has not been reported, and it could be interesting to understand the possible delayed effects of accumulated training demands or accumulated poor well-being reports in the following training process. Possibly, better identification of such relationships may provide useful insight to coaches and parents for being attentive to some signals in players [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…This has not been reported, and it could be interesting to understand the possible delayed effects of accumulated training demands or accumulated poor well-being reports in the following training process. Possibly, better identification of such relationships may provide useful insight to coaches and parents for being attentive to some signals in players [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their indicated psychological attributes were compared with their sports abilities. Those athletes that indicated that they possessed personal integrity such as honesty and responsibility also demonstrated social cohesion which linked to what was called task cohesion, meaning team cohesion in this case (Berengui et al 2022). It was expected that team cohesion would continue as athletes aged and continued to take part in sports.…”
Section: Discussionmentioning
confidence: 94%
“…The close link between moral education and sports practice has been confirmed (Bruner et al, 2018), and provided that sport is well organized, it can be an excellent means of transmitting positive social and personal values to children and adolescents (Berengüí & Garcés de Los Fayos, 2007;Light & Harvey, 2015). Therefore, it is imperative that clubs and coaches work to ensure the promotion of value systems that foster the task orientation of the athlete, and promote these positive values (Berengüí et al, 2022). Unlike elite sport, sport at young ages should tend to explicitly advocate values that go beyond victory, bringing together diverse educational experiences, such as the development of sport skills, leadership and teamwork (English, 2018).…”
Section: Discussionmentioning
confidence: 99%